1988
DOI: 10.1007/bf01287780
|View full text |Cite
|
Sign up to set email alerts
|

Periclase-chromite refractories for steel-teeming ladles with ladle treatment of the steel

Abstract: Highly effective desulfurization of steel is obtained in ladles with linings of lime-Periclase and periclase-lime heat treated parts with a pitch or tar binder and the ladle life reaches 30-60 heats.At present measures are being taken for organization of the production of such refractories in shops for the production of converter parts for steel plants.In accordance with the general plan of development of the iron and steel industry a significant increase in ladle treatment of steel is planned. In connection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In view of the fact that effective works [i0, ii] on use of heat treated periclase-lime parts with resin and pitch binders have not yet been completed as the result of unsolved production and organizational questions, periclase-chromite refractories are used for the lining of ladles with ladle treatment. The authors of [12] showed that their life in the slag belt and bottom is twice the life of high-alumina parts.…”
mentioning
confidence: 98%
“…In view of the fact that effective works [i0, ii] on use of heat treated periclase-lime parts with resin and pitch binders have not yet been completed as the result of unsolved production and organizational questions, periclase-chromite refractories are used for the lining of ladles with ladle treatment. The authors of [12] showed that their life in the slag belt and bottom is twice the life of high-alumina parts.…”
mentioning
confidence: 98%
“…Such conditions of treatment of the steel are very unfavorable for service of refractories in vacuum degasser legs [1][2][3][4][5]. Such conditions of treatment of the steel are very unfavorable for service of refractories in vacuum degasser legs [1][2][3][4][5].…”
mentioning
confidence: 99%